Digital literacy and communicative competence among academic leaders : post-COVID-19 study - Saeed, Halah Kamal; Norizan Abdul Razak,; Ashinida Aladdin, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Communicative competence represents an academic leader's ability to use language effectively. However, to date, communicative competence among academic leaders is not as effective as expected. This research aims to explore the affective factors hindering the academic leaders' communicative competence, identify the cultural factors affecting their communicative competence, and investigate the impact of using technology in developing communicative competence during the Covid-19 pandemic. This qualitative study employed semi-structured interviews with nine academic leaders from different universities in Iraq. It adopts four theories: communicative competence, leadership competence, communication and planned behaviour for the basis and guidance for data collection, data analysis, and interpretation. The qualitative data were transcribed and analysed using thematic analysis. It was found that the following Key factors, such as digital literacy became crucial during lockdown because of COVID-19. All meetings and conferences adopt online mode instead of physical appearance. In such a situation, majority respondents mentioned that communicative competence has proven helpful in problem-solving and developing critical skills. The respondents have proposed a framework for developing academic leaders' communicative competence for digital literacy post-Covid -19. Such as training to use digital tools for language usage, monitoring the electronic examination process more efficient and initiatives for communication competence.